If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 3x + -9 + 6x = -18 Reorder the terms: -9 + 3x + 6x = -18 Combine like terms: 3x + 6x = 9x -9 + 9x = -18 Solving -9 + 9x = -18 Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '9' to each side of the equation. -9 + 9 + 9x = -18 + 9 Combine like terms: -9 + 9 = 0 0 + 9x = -18 + 9 9x = -18 + 9 Combine like terms: -18 + 9 = -9 9x = -9 Divide each side by '9'. x = -1 Simplifying x = -1
| 7x-36=-100 | | -6x^3+23x^2-28x+11=0 | | 6+7=1 | | 7x-36=-1000 | | 10-5=12 | | 0.6x-0.6=0 | | 13r-11r=2 | | 0.6x+11=7 | | 5*1/6 | | 3(2x+3)=90 | | 10(v+3)-2v=4(2v+4)-23 | | 7(9-5h)=31 | | 14x+5y=78 | | 8h-6h=6 | | x^3/4=8 | | y=9+13x | | x+(x*.0865)=25 | | 9s-4s=10 | | 4xn+2-6=18 | | v/5-2=6 | | y^(5/4)=7 | | 8y=56-8x | | 8-6x=3x^2-10x+4 | | 5u-2u=18 | | 8a/b^5 | | 36+4X=60 | | 8y=8x-56 | | y=5y+16 | | 6x+2=4x-y | | 4(a^2+11a-48)=0 | | -9+7r=-5r | | 10t-.83t^2=14 |